2017
DOI: 10.1055/s-0037-1598181
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Children with HIV Infection—A Cross-Sectional Study from South India

Abstract: Assessment of health-related quality of life (HRQoL) in children with HIV is crucial to improve the psychosocial well-being of this vulnerable population. The objective of this study was to assess the HRQoL of children with HIV infection aged between 5 and 18 years. The study was conducted in 144 children with HIV attending an antiretroviral therapy (ART) center in Karnataka to assess the HRQoL, using the PedsQL questionnaire. Total 144 children were included in the study, who had HRQoL with good physical (75.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
(29 reference statements)
4
8
1
Order By: Relevance
“…Furthermore, although most of the study participants had two living parents, good immunological status [CD4 lymphocyte count, viral load] there was no significant association between social status, immunological status, and better HRQoL, suggesting that other factors play a more important role for the well-being of children living with HIV. These findings support the results from previous studies (27,28,30,35). The strength of this study is the in-depth data obtained about the views of HRQoL obtained from both parents and children.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, although most of the study participants had two living parents, good immunological status [CD4 lymphocyte count, viral load] there was no significant association between social status, immunological status, and better HRQoL, suggesting that other factors play a more important role for the well-being of children living with HIV. These findings support the results from previous studies (27,28,30,35). The strength of this study is the in-depth data obtained about the views of HRQoL obtained from both parents and children.…”
Section: Discussionsupporting
confidence: 93%
“…Our results confirm previous evidence about the poor psychological wellbeing of children and adolescents who live with HIV. Lower psychosocial scores observed in this study are in accordance with reports of other researchers who studied children living with HIV (28,(30)(31)(32)(33)(34)(35). Although Gupta et al (27) reported better psychosocial HRQoL in the study population in South India suggesting that this difference might be due to family and socio-cultural practices in the community.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations